Killing of melanoma cells and their metastases by human lactoferricin derivatives requires interaction with the cancer marker phosphatidylserine - Riedl, Sabrina (Springer Netherlands, 2014)
Despite favorable advancements in therapy cancer is still not curative in many cases, which is often due to inadequate specificity for tumor cells. In this study derivatives of a short cationic peptide derived from the human host defense peptide lactoferricin were optimized in their selective toxicity towards cancer cells. We proved that the target of these peptides is the negatively charged membrane lipid phosphatidylserine (PS), specifically exposed on the surface of cancer cells. We have studied the membrane interaction of three peptides namely LF11-322, its N-acyl derivative 6-methyloctanoyl-LF11-322 and its retro repeat derivative R(etro)-DIM-P-LF11-322 with liposomes mimicking cancerous and non-cancerous cell membranes composed of PS and phosphatidylcholine (PC), respectively. Calorimetric and permeability studies showed that N-acylation and even more the repeat derivative of LF11-322 leads to strongly improved interaction with the cancer mimic PS, whereas only the N-acyl derivative also slightly affects PC. Tryptophan fluorescence of selective peptide R-DIM-P-LF11-322 revealed specific peptide penetration into the PS membrane interface and circular dichroism showed change of its secondary structure by increase of proportion of β-sheets just in the presence of the cancer mimic. Data correlated with in vitro studies with cell lines of human melanomas, their metastases and melanocytes, revealing R-DIM-P-LF11-322 to exhibit strongly increased specificity for cancer cells. This indicates the need of high affinity to the target PS, a minimum length and net positive charge, an adequate but moderate hydrophobicity, and capability of adoption of a defined structure exclusively in presence of the target membrane for high antitumor activity.